Perbandingan Nilai Simpangan Horizontal yang Menggunakan Bresing Tipe Diagonal dengan Inverted V dalam Menahan Gaya Lateral pada Studi Kasus Hotel Loji Kridanggo Boyolali - Ratu Adila; Erno Widayanto; Ketut Aswatama Wiswamitra (Rekayasa Sipil, 2023)
Application of a bracing skeletal system is an additional steel structure that can strengthen a column by transferring weights and force to the received column. The broad use of flensa steel bracing type v diagonally and inverted gradually on each floor. It is possible to determine the junction of the junction if the building is brewed and not braced. The junction to cross section of the building does not use bracing, which USES bracing type v diagonal and inverted is 0.385:0.321:0.294. Bracing inverted type v is more rigid and sturdy than bracing diagonal types shown by the deviation of horizontal bracing the inverted type v smallest and volume 12.5 percent greater than bracing the type diagonal.